Efisiensi Penggunaan Faktor Produksi Usahatani Kunyit Di Kecamatan Lampanah Lengah, Kabupaten Aceh Besar - Ismayani Ismayani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. The objectitive of this research is to find the factors impacted of turmeric farm and the efficiency of production factor allocation was efficient or not. This research used survey method. The research was tested by Cobb Douglass production function analysis. The result of research shows that area factor allocation 0,30 hectare not efficien. Showing that area factor necessary to increased anyway the income of the farmer increasing. And the allocation of labor factor 17,43 HKP per season be decreased cause not efficien and can be high the labor, over production and marginal production value lower.